Study of the effect of surface roughness on droplet spreading behavior using CFD modeling - Bin Ramli, M.S. (Trans Tech Publications Ltd, 2014)
Water droplet spreading has been simulated at impact velocity of 3.0 m/s, 1.5 m/s and 0.5 m/s on surfaces with texture of âtriangleâ, âsquareâ, âcurveâ as well as smooth surface of aluminum. Higher impact velocity induced the droplet to spread faster and has a bigger diameter. At high impact velocity, spreading factor cannot be determined due to splashing and droplet break ups. In addition, at 1.5 m/s the phenomenon of splashing was found to be almost absent except on the surface with âsquareâ texture. âSquareâ surface tends to splash earlier compared to other surfaces and is followed by âtriangleâ, âcurveâ and smooth surface. At low impact velocity, the smooth surface has the highest spreading factor and followed by âtriangleâ, âsquareâ and âcurveâ surface. Â© 2014 Trans Tech Publications, Switzerland.